2012
DOI: 10.1097/lgt.0b013e3182403d18
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Persistence of Low-Grade Cervical Squamous Intraepithelial Lesions in Women Living With Human Immunodeficiency Virus

Abstract: Antiretroviral treatment reduced the risk for progression and persistence of LSIL in HIV-infected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The risk of developing SIL and HSIL was found to be higher in HIV positive women with severe immunosuppression, which is in support of previous studies from southern Africa, North America and Asia that reported higher prevalence of SIL among severely immune-compromised women [13]–[16]. The independent association between SIL and severe immunosuppression was retained after controlling for the use of antiretroviral drugs, confirming the independent effect of severe immunosuppression with poor clearance of HPV from cervical cells and eventual transformation of SIL to invasive cancer [14], [17], [18], Agaba et al [19] and Sewande et al [22] reported that the immunosuppressive effect, measured by the decrease in CD4 cell count, is the greatest predictor of cervical lesion development in HIV-positive women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The risk of developing SIL and HSIL was found to be higher in HIV positive women with severe immunosuppression, which is in support of previous studies from southern Africa, North America and Asia that reported higher prevalence of SIL among severely immune-compromised women [13]–[16]. The independent association between SIL and severe immunosuppression was retained after controlling for the use of antiretroviral drugs, confirming the independent effect of severe immunosuppression with poor clearance of HPV from cervical cells and eventual transformation of SIL to invasive cancer [14], [17], [18], Agaba et al [19] and Sewande et al [22] reported that the immunosuppressive effect, measured by the decrease in CD4 cell count, is the greatest predictor of cervical lesion development in HIV-positive women.…”
Section: Discussionsupporting
confidence: 89%
“…Despite availability of studies that examined the effects of antiretroviral drug use on the course of cervical lesions in HIV positive women, the impact of the use of antiretroviral drug on the course of cervical lesions remains somewhat unclear [7][13]. While some studies [10][12], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies reported the association of ART with cytology diagnosed SIL incidence, 15 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 and two studies with histology diagnosed HSIL-CIN2+ incidence 17 , 63 from a combined total of 5096 women ( table 1 ). We included ten studies 31 , 54 , 55 , 61 , 64 , 65 , 66 , 67 , 68 , 69 for cytology diagnosed SIL progression from a combined total of 6212 women, and ten studies 15 , 31 , 54 , 61 , 64 , 67 , 68 , 70 , 71 , 72 for regression of histology diagnosed CIN or cytology diagnosed SIL from a combined total of 5261 women ( table 1 ). Only one study reported the regression from histological CIN grade 1 to normal.…”
Section: Resultsmentioning
confidence: 99%
“…35 In terms of evolution of SIL lesions, data are more supportive of an effect of cART on the progression of SIL lesions. 33, 36 Minkoff and colleagues 37 showed that, among 286 women enrolled in the WIHS cohort who initiated cART, adherence to cART resulted in a significant reduction of SIL (OR 5 2.25; 95% CI 5 1.03-4.93) compared with before cART. Further longitudinal studies with more uniform methods and outcome definitions are needed to assess the effect of cART on HPV infection as well as SIL progression, persistence, or regression.…”
Section: Effect Of Cart On Hpv Persistence and Evolution Of Precancermentioning
confidence: 96%